(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper complements an earlier work by the author, which was published in MHNH 9, 2009. A rite performed by the Mysians of Asia minor is revealed from some information contained in the treatise de fluviis by Pseudo-Plutarch. Despite the distortion introduced by paradox-graphical writings, we are able to perceive that it is a divination ritual, of which grasshoppers are protagonist, for the purpose of predicting the annual grain harvest. Undoubtedly, the origin of this type of augury lies in the Indo- European substrate of the Mysians, both the ethnic group resident in Europe (in the vicinity of the Danube) and that who emigrated to Anatolia. Its analysis facilitates the reconstruction of new facets of the Celtic “augurio de los langostos” (grasshoppers augury) from the Iberian Peninsula and it also permits us to reassess the role of certain elements ascribed to the rite (bread, psychoactive substances).